2016
DOI: 10.1128/jvi.00557-16
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic CD8 + T-Cell Defense in Simian Immunodeficiency Virus Control by Acute-Phase Passive Neutralizing Antibody Immunization

Abstract: Identifying human immunodeficiency virus type 1 (HIV-1) control mechanisms by neutralizing antibodies (NAbs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 61 publications
3
45
0
Order By: Relevance
“…In our SIV challenge-NAb passive immunization model, we found that early (day 7) passive polyclonal NAb infusion in SIV mac239 -challenged rhesus macaques resulted in elevated myeloid DC-associated viral loads (Yamamoto et al, 2007), temporally followed by elevation of Gag-specific polyfunctional CD4 + T-cell responses and increased in vitro viral suppressive activity in CD8 + cells (Yamamoto et al, 2009) (Table 1 and Figure 1D). Extended from such findings, in this model we recently identified that these NAb-mediated CD8 + cells also acquired enhanced suppressive activity against a panel of immunodominant CTL escape mutants, providing stringent T cell-based SIV control for up to 2 years without accumulation of viral CTL escape mutations (Iseda et al, 2016). This poses a possibility that the total virus-specific CTL population in NAb-infused animals became resistant against arousal of SIVs with CTL escape mutations in vivo , contributing to the prevention of CTL escape mutation accumulation.…”
Section: Adaptive Immune-cell Boosting By Passive Nabsmentioning
confidence: 65%
See 1 more Smart Citation
“…In our SIV challenge-NAb passive immunization model, we found that early (day 7) passive polyclonal NAb infusion in SIV mac239 -challenged rhesus macaques resulted in elevated myeloid DC-associated viral loads (Yamamoto et al, 2007), temporally followed by elevation of Gag-specific polyfunctional CD4 + T-cell responses and increased in vitro viral suppressive activity in CD8 + cells (Yamamoto et al, 2009) (Table 1 and Figure 1D). Extended from such findings, in this model we recently identified that these NAb-mediated CD8 + cells also acquired enhanced suppressive activity against a panel of immunodominant CTL escape mutants, providing stringent T cell-based SIV control for up to 2 years without accumulation of viral CTL escape mutations (Iseda et al, 2016). This poses a possibility that the total virus-specific CTL population in NAb-infused animals became resistant against arousal of SIVs with CTL escape mutations in vivo , contributing to the prevention of CTL escape mutation accumulation.…”
Section: Adaptive Immune-cell Boosting By Passive Nabsmentioning
confidence: 65%
“…It remains to be clarified whether the slightly earlier moment of NAb infusion derives the protection not obtained by early cART, or if other effector functions of NAbs unavailable by drugs mediate the protective effect. Our model of an acute-phase single NAb infusion resulting in sustained SIV control (Iseda et al, 2016) is most suggestive for the latter. Implications are also provided by a report showing that a combined bNAb single shot at day 10 post-SHIV infection derives protective effects substituting and comparable to that of a daily ART regimen for the next 11 days (Bolton et al, 2016).…”
Section: Comparison Between Passive Nabs and Drug Therapymentioning
confidence: 65%
“…1a ) for the present study. Seventeen macaques of the twenty had been used in our previous SIV challenge experiments 20 36 37 38 39 40 41 . Animals with varieties of MHC-I haplotypes including a protective MHC-I haplotype, 90-010-Id (D) (ref.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of SIV-infected adult macaques with neutralizing polyclonal IgG (SIVIG) effectively controlled viremia and accelerated B cell responses resulting in reduced pathogenesis [18]. SIVIG-treatment of infected macaques was also shown to drive enhanced CD4 + and CD8 + T-cell responses allowing a T cell-based SIV control for up to 2 years [19][20][21]. Similarly, early treatment of SHIV-infected infant macaques with polyclonal HIVneutralizing IgG accelerated a de novo neutralizing antibody production that was associated with disease protection [22,23].…”
Section: Hiv-1 Bnabs Elicit Antiviral Host Immune Responsesmentioning
confidence: 99%